Antiviral properties of propolis ethanol extract against norovirus and its application in fresh juices. (December 2021) - Liao, Ningbo; Sun, Liang; Wang, Dapeng; Chen, Lili; Wang, Jikai; Qi, Xiaojuan; Zhang, Hexiang; Tang, Mengxuan; Wu, Guoping; Chen, Jiang; Zhang, Ronghua
Abstract: Human noroviruses (HuNoVs) outbreaks have been linked to contaminated fresh-cut produce. Propolis has been used as a folk medicine because of its extensive bioactivity and antimicrobial properties. The aim of this study was to investigate the antiviral properties of propolis water extracts (PWE) and propolis ethanol extracts (PEE) against noroviruses, and its application in fresh-cut produce. Extraction yields, total phenolic content, total flavonoid, and soluble carbohydrate content of the propolis extracts were measured to estimate their antiviral compounds. The HuNoV GII.4 and its surrogates (murine norovirus MNV-1 and bacteriophage MS2) were used to evaluate the anti-noroviral activities of propolis extracts. The polyphenol-rich extract (PEE) showed better antiviral activities than PWE. Time-of-addition experiments and TEM images suggested that PEE denatured the viral capsid protein and likely prevented adsorption and internalization of viruses into cells. The application of PEE for natural preservative in fresh juices was also analyzed. After 30 min of treatment of the four different juices, 500 μg/mL PEE reduced MNV-1 and MS2 titers by > 3.0 log10. Therefore, the PEE containing high amounts of polyphenol improved the safety of fresh juices and could be potential candidates for the development of novel natural antiviral preservative for fresh juices. Highlights: Propolisethanol extracts (PEE) contain high amount of polyphenol compounds. PEE show significant antiviral effects against norovirus and its surrogates. PGM–ISC–RT-qPCR is a useful method to estimate the infectivity of HuNoVs. PEE denatured viral capsid protein and prevented adsorption of viruses into cells. PEE could reduce the titers of MNV-1 and MS2 in juices significantly.